2016
DOI: 10.1074/jbc.m115.683185
|View full text |Cite
|
Sign up to set email alerts
|

The Sensorless Pore Module of Voltage-gated K+ Channel Family 7 Embodies the Target Site for the Anticonvulsant Retigabine

Abstract: KCNQ (voltage-gated K؉ channel family 7 (Kv7)) channels control cellular excitability and underlie the K ؉ current sensi- Members of the voltage-gated K ϩ (Kv) 5 channel family 7 (Kv7, otherwise known as KCNQ) are key determinants of cellular excitability in the heart (Kv7.1) and brain (Kv7.2-7.5) (1, 2). There is no crystal structure for any member of Kv7 family, although they constitute prominent targets of clinically relevant drugs, and their dysfunction is implicated in a number of human diseases (1-3). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 38 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…Here, for the first time, we provide an example of hysteresis in the activity of a K V channel that directly affects the channel’s pharmacology under physiological conditions. In line with recent findings on the action of Retigabine on the isolated pore of K V 7 channels ( Syeda et al, 2015 ), our observations clearly show that the stabilized open state of the K V 7.2/K V 7.3 channel is the target for the action of the anticonvulsant Retigabine. These findings have several implications.…”
Section: Discussionsupporting
confidence: 92%
“…Here, for the first time, we provide an example of hysteresis in the activity of a K V channel that directly affects the channel’s pharmacology under physiological conditions. In line with recent findings on the action of Retigabine on the isolated pore of K V 7 channels ( Syeda et al, 2015 ), our observations clearly show that the stabilized open state of the K V 7.2/K V 7.3 channel is the target for the action of the anticonvulsant Retigabine. These findings have several implications.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, such drugs can partially compensate for the decrease in M-currents caused by PI(4,5)P 2 depletion (Zhou et al, 2013). Retigabine stabilizes the channels' open states as it increases the dwell time of open events (Tatulian and Brown, 2003;Syeda et al, 2015). Consistently, Retigabine also decreases the deactivation rate of K V 7.2/K V 7.3 channels (Main et al, 2000;Linley et al, 2012;Corbin-Leftwich et al, 2016;Yau et al, 2018).…”
Section: Pi(45)p 2 Depletion Hampers the Activity-dependent Stabilizmentioning
confidence: 89%
“…Although the mechanism underlying this action remains unclear, single channel recordings show that Retigabine increases the lifetime of open state events of K V 7.2/K V 7.3 channels, while decreasing the dwelling-time of closed channel events (Tatulian and Brown, 2003). Further, the mean-open-time of the isolated pore of K V 7.3 channel increases in the presence of Retigabine (Syeda et al, 2015). Furthermore, the deactivation rate of both K V 7.2/K V 7.3 and K V 7.3 channels decreases in the presence of Retigabine (Wickenden et al, 2000;Corbin-Leftwich et al, 2016;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a recent study showed that NMDAR channels were mechanically responsive to fluid shear stress in the absence of agonists (Maneshi et al, 2017), which seems also to indicate a physiological role for NMDAR in the glymphatic clearance pathway in the brain (Jessen and Kotz, 2015; Cox et al, 2019; Martinac and Bilston, 2019). Moreover, like mechanosensitive MscS, MscL, TREK-1, TREK-2, TRAAK, Piezo1, and OSCA channels (Kloda et al, 2007a; Brohawn et al, 2014; Cox et al, 2016; Syeda et al, 2016; Murthy et al, 2018), the NMDAR channel protein could be reconstituted into liposomes and activated by stretching liposome patches (Kloda et al, 2007a), which indicates that NMDAR is inherently mechanosensitive meaning that lipid-protein interactions are sufficient for the channel activation by mechanical force.…”
Section: Mechanisms Of Nmdar Activation #3: Mechanosensitivitymentioning
confidence: 99%
“…What is the consequence of these findings for the mechanosensitivity of NMDA receptors? The bonus of these findings is that local curvature on the scale of tens of nanometers can be influenced by a host of proteins, lipid types and unilateral insertion of physiologically active amphipathic molecules, such as arachidonic or lysophosphatidic acid (Figure 1; Zimmerberg and Kozlov, 2006; Kloda et al, 2007b; Frisca et al, 2012; Syeda et al, 2016). Moreover, the list of amphipathic molecules produced and released in physiological settings that could modify NMDAR channel function is potentially very long.…”
Section: Membrane Curvature As a Possible Mechanism Of Nmdar Activatimentioning
confidence: 99%